Natural Syntax: English dependent clauses - Orešnik, Janez (Adam Mickiewicz University, 2007)
Natural Syntax is a developing deductive theory. The naturalness judgements are couched in naturalness scales, which follow from the basic parameters (or “axioms”) listed at the beginning of the paper. The predictions of the theory are calculated in the deductions, whose chief components are a pair of naturalness scales and the rules governing the alignment of corresponding naturalness values. Parallel and chiastic alignments are distinguished, in complementary distribution. Chiastic alignment is mandatory in deductions limited to unnatural environments. This paper wishes to acquaint the reader with the current version of Natural Syntax. By way of exemplification the paper covers selected topics within English dependent clauses.